Developing Tri Kaya Parishida Based Blended Learning Media Using Adobe Captive for Probstat Courses - Indrawan, I P. Oktap; Pramana, M. Indra Wira; Gunawan, K. Dwi Hendratma (Journal of Education Reseach and Evaluation, 2019)
The objectives of this study ware to: (1) Design TKP based BLM that was based on the needs of students and lecturers for probability and statistics courses at the Informatics Management Department of Politeknik Ganesha Guru; (2) Measure the quality of TKM based BLM that was based on the needs of students and lecturers for probability and statistics courses in the Informatics Management Department of Politeknik Ganesha Guru; (3) Determine student and lecturer responses to the implementation of the TKM based BLM that was based on the needs of students and lecturers for probability and statistics courses in the Informatics Management Department of Politeknik Ganesha Guru; (4) Determine student learning outcomes before and after the implementation of the TKP based BLM in the teaching and learning process. The research conducted at the Politeknik Ganesha Guru. The subjects of the study were students and lecturers at the Politeknik Ganesha Guru who volunteered in the product trials and run trials in this study. The object of this research was the TKM based BLM developed for the Probstat course. The type of research chosen was Research and Development (R&D). Based on the Result and Discussion, it could be concluded that: (1) the TKM based BLM product was developed based on the needs of students and lecturers for probability and statistical courses through the R&D method; (2) the quality of BLM based TKP products scored 91.33, qualified as very good, provided by the content experts and media experts rated the product 91.67 qualified it as very good; (3) students and lecturers responses to the implementation of the TKM based BLM were given an average score of 97.92 qualified as very good; (4) there is a significant difference between the pretest and posttest trials using the TKM based BLM (sig. 0,000 <0.005), an increase in the value of the pretest value 33.74 to 73.6 posttest.